El ejercicio de la abogacía en España - Areta Martínez, María (2019)
The present work has as its objective to state the most significant changes that the practiceof law has been experimenting in the 21st century as well as to discuss its challengesin a globalized society in constant evolution. In the last years, Spanish legal ordainmenthas experienced various reforms with the purpose of responding to needs posed in thepractice of law now-a-days. Following, the author will cover all of these aspects.